Structural Inequality in the Philippines: Oligarchy, (Im)mobility and Economic Transformation - Tuaño, Philip Arnold (Archīum Ateneo, 2019)
Over the past four decades, the Philippines has achieved significant advances in its growth performance and has undergone a series of transformations in its political, economic and social structures. However, while average incomes have risen, the country’s record in terms of generating quality employment and reducing poverty and inequality has been disappointing. High levels of income inequality and social exclusion have persisted in the country, even as the rate of upward socio-economic mobility, at least compared to its ASEAN neighbours, has been low. Moreover, new evidence suggests that key forms of wealth inequality have been rising. These trends are caused not only by poor human and physical investment as well as the adverse effects of premature deindustrialization, but also by the dynamics of an oligarchical political economy in which political dynasties and family-linked conglomerates have substantially curbed the capacity of non-elite formations and players to assert more developmental policy regimes and substantive democratization.